2005
DOI: 10.4315/0362-028x-68.4.696
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella in Dairy Operations in the United States: Prevalence and Antimicrobial Drug Susceptibility

Abstract: Salmonella serotypes are important foodborne pathogens of humans that can be acquired through consumption of contaminated meat and dairy products. Salmonella infection also can be a significant animal health issue. As part of a national study of U.S. dairy operations conducted between March and September 2002, fecal samples were collected from representative cows in 97 dairy herds in 21 states and were cultured to determine the prevalence of Salmonella shedding. Salmonella was recovered from the feces of at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 18 publications
9
49
5
Order By: Relevance
“…11.5 and 7.1% conducted in Kombolcha and Debre Zeit, Ethiopia (Minte et al, 2011;Daniel et al, 2003), respectively. This study is in agreement with the report of Blau et al (2004) who indicated that prevalence of Salmonella spp. was recorded in 7.3% in Dairy Operations in the United States (USA).…”
Section: Prevalence Of Salmonella Spp In the Milk Samplesupporting
confidence: 94%
See 1 more Smart Citation
“…11.5 and 7.1% conducted in Kombolcha and Debre Zeit, Ethiopia (Minte et al, 2011;Daniel et al, 2003), respectively. This study is in agreement with the report of Blau et al (2004) who indicated that prevalence of Salmonella spp. was recorded in 7.3% in Dairy Operations in the United States (USA).…”
Section: Prevalence Of Salmonella Spp In the Milk Samplesupporting
confidence: 94%
“…This is also comparable with the result conducted in USA (Blau et al, 2004). In line with this, the result of these antimicrobial agents, like ciprofloxacin and gentamycin, is covenant with the study done in Asella town, Ethiopia (Takele et al, 2016) and norfloxacin, in Harrer (Ayalu et al, 2011) and in Sudan (Fadlalla et al, 2012).…”
Section: Antimicrobial Susceptibility Testingsupporting
confidence: 87%
“…Hence lactating cows could be potential sources of Salmonella infection for individuals working in dairy farms and for the community at large. Fecal prevalence of Salmonella among lactating dairy cattle in the current study was 7.7% (7/91) which is interestingly similar with the fecal Salmonella isolation rate of 7.7% in lactating cows and in contact humans in dairy farms of Addis Ababa (Zelalem Addis et al, 2011) and 7.3% in dairy cows in USA (Blau et al, 2005). However, it is lower than the fecal Salmonella isolation rate of 9.7% in United States (Callaway et al, 2005).…”
Section: Discussionsupporting
confidence: 48%
“…This result strongly disagrees with the current study in which 96.4% and 39% of the isolates were resistant to tetracycline and ampicillin, respectively. Resistance rates to ampicillin and tetracycline is very high when compared to results documented in America (Blau et al, 2005) reported as 4.4 % and 12.2 % resistance levels, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…This is in agreement with the apparent correlation between antimicrobial resistance and the presence of clinical disease in dairy cattle. Studies of fecal Salmonella shedding among healthy cattle across the United States have shown antimicrobial resistance to be uncommon (Wells et al, 2001;Blau et al, 2005;Ray et al, 2007), but multidrug resistance was found to be highly prevalent among isolates from cattle with clinical signs of salmonellosis in the northeastern United States (Cummings et al, 2009). A similar phenomenon has also been observed in people, as infections with resistant Salmonella strains tend to be more severe and lead to higher rates of hospitalization than those caused by susceptible strains (Helms et al, 2002(Helms et al, , 2004Varma et al, 2005aVarma et al, , 2005b.…”
Section: Figmentioning
confidence: 86%